Not Only about “Agents”!... Old and new decisions without theological vision? Aspects related to exploring the past, remembrance and reconciliation in the Reformed Church of Hungary - FAZAKAS, Sándor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
Approximately twenty-five years after the social and political changes of 1989 in Central and Eastern Europe, the question remains for the Hungarian Reformed Church: what are the possible consequences of not attaching sufficient importance to the problems of responsibility for history and political/moral sin? Obviously, the question cannot be simplified to cover only the agent issue, i.e. judging the open or undercover collaboration between ministers, church leaders and other clerical staff and the oppressive political power. On the one hand, this study underlines why such a collaboration with the totalitarian regime can be considered theologically absurd, i.e. a sin, even if some psychological or political arguments might serve as an explanation. On the other hand, it argues that sin and moral conflict of the self cannot only take place in situations where people driven by fear or suppressed by or giving in to blackmailing or driven by selfish interests collaborated with the regime, or were silent when they should have protested, or where they rejected solidarity with those persecuted, or failed to criticise the political system or the political compromises of the church. We also have to talk about historical sins, where the church relinquished a critical analysis of the historical and political reality of society and failed to have or obscured any clear theological vision. This lack of theological information and the narrow perception of social reality ultimately left only two alternatives for the church: it was either enthusiastic about the laudable, “great objectives” of the given political regime, or made moral/theological and political “allowances”, supposedly to avoid presumably worse solutions. Well, the failure to interpret reality from a spiritual/theological perspective, the striking of seemingly harmless compromises as well as the lack of solidarity with the members of the strong community and the church led people to become tangled up in the jungle of the conspiracy sins of collaboration. This does not lessen the weight of individual responsibility, but such a systemic approach to the problem and the social/theological analysis of past sins could explore the theological/ethical interpretative framework that helps to judge individual choices. Thereafter, the study wishes to offer some examples of how the encounter with the past can unfold “in the space of the church”. The ethical dimensions of exploring the past, establishing a culture of sympathy, making remembrance and penitence possible without constraints and driven by free will, furthermore dealing with the process of conciliation in its complexity, taking legal, political and religious/moral aspects into account, could promote the co-habitation of generations, and be determined by a joint search for the historical truth as well as demand for a reconciled community rather than harming others and causing further injuries.